Ariosto, poeta della forma: dalle lezioni giovanili alla Storia della letteratura italiana di Francesco De Sanctis - Luca Ferraro (Laboratoire Italien)
This article focuses on the evolution of the thinking of De Sanctis about the Renaissance and the Orlando Furioso in three steps: the early Neapolitan lessons, the Lezioni Zurighesi and the History of Italian Literature. The analysis deals with three key aspects: the relationship between epic and chivalry, the unity of plot, and form. The purpose is to demonstrate how the opinions of De Sanctis change less radically than we may imagine, as some fixed points remain unchanged throughout time. What significantly changes is the perspective through which these points are interpreted.